Pengembangan Sistem Informasi Pelaporan Perjalanan Dinas Menggunakan Metode Rapid Application Development (RAD) - Nolly Pialewi; Rudy Hartono (PPPM Institut Teknologi Pagar Alam, 2026)
Microsoft Excel is still utilized by the Department of Cooperatives, Small and Medium Enterprises, and Trade (DISKUMDAG) of Landak Regency as the primary tool for data management and official travel reporting. This condition leads to difficulties in data retrieval and updating, risks of errors in cost calculation and data duplication, as well as an unintegrated process of report preparation and budget usage monitoring. As a resolution, a web-based official travel reporting information system was developed to facilitate the tasks of the Secretariat Division admin in managing official travel reporting data, while also providing information that supports the decision-making process for the Head of the Department. The Research and Development (R&D) approach was employed in this study, with the Rapid Application Development (RAD) method encompassing three stages, namely requirement planning, design workshop, and implementation. The Laravel framework with MySQL database was used as the foundation for system development. System testing was conducted through Black Box Testing and User Acceptance Testing (UAT) involving 20 individuals, consisting of 10 individuals with competence in the IT field and 10 employees of DISKUMDAG Landak Regency. The results of the Black Box Testing indicated that all system features functioned properly, while through UAT, a user acceptance rate of 90.92% was obtained. Based on the overall testing results, it can be concluded that the system has been well accepted by users and is considered to have met the requirements in the process of managing and reporting official travel